Concluding Contracts for the Sale of Goods Through E-Commerce Platforms and Recommendations for the Improvement of Vietnamese Law - Hà, Lê Thị Tuyết (Journal of Ecohumanism, 2024)
The conclusion of contracts through electronic means has evolved and is now applied across various economic sectors. Contracts for the sale of goods are no exception and are frequently concluded on e-commerce trading platforms. Although commercial law includes provisions regulating the conclusion of contracts for the sale of goods through this method, practical experience indicates that some provisions are inconsistent and do not align with the general regulations on contract conclusion in the Civil Code. This results in practical issues during contract implementation. This article analyzes several practical issues in concluding contracts for the sale of goods on e-commerce trading platforms and proposes recommendations for improvement.